EFFICIENCY OF PRE-HARVEST APPLICATION OF CLOROTALONIL, THIOPHANATE-METHYL AND TETRACONAZOLE ON PEACH BROWN ROT CONTROL - BLOOD, Renato Rezende Young; ROVEDA, Luís Fernando; MAY DE MIO, Louise Larissa; MOREIRA, Luciene Martins (Scientia Agraria, 2007)
Peach orchards are affected annually by brown rot caused by the fungus Monilinia fructicola, leading to yield loss. The reduction of the inoculum by means of chemical treatment is one of the ways to control it. Thus, this work tested the efficiency of pre-harvest application of fungicides to control brown rot in peach crop. The experiment was conducted in a commercial orchard of Lapa – PR. The experimental design was randomized blocks, with eight treatments: check, clorotalonil (100 and 150 g 100 L-1), tetraconazol (75 and 100 g 100 L-1), thiophanate-methyl (60 and 85 g 100 L-1) and mancozeb (200 g 100 L-1) and four replications. For the evaluation at harvest, all the fruits picked in the central region of each parcel were considered, and the total number of fruit picked and the number of fruit presenting brown rot in each of the harvest dates were also evaluated. Furthermore, for each harvest date samples of 10 healthy fruit were placed in alveolus trays, kept at room temperature for 3 and 5 days, and evaluated for disease incidence. Thiophanate-methyl and tetraconazole in both dosages and clorotalonil in the highest dosage were the most effective to control brown rot in the field. The systemic products, thiophanate-methyl and tetraconazole presented the highest post-harvest residual effect.